THE SHIFTING OF FACE TO FACE LEARNING TO DISTANCE LEARNING DURING THE PANDEMIC COVID-19 - Almanar, Muhammad Abduh (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
Abstract Using a qualitative research methodology, this study is expected to answer on how students’ responses toward distance learning during the pandemic (Covid-19). Moreover, this study also provided factual data, suggestions and advices on how distance learning implemented. A qualitative research methodology was applied to 30 students of University of Muhammadiyah (UMT) Tangerang after 14 meeting of distance learning using Google Classroom. Questionnaires were distributed online to see how students’ responses toward a distance learning. The findings proved that there were significant impacts to the students’ learning performance such as computation skills, autonomous learner and critical learner. Besides, negative impact arose due to connectivity, compatible devices, basic skill of computation and also student-teacher communication. Keywords: distance learning, students’ learning responses and experience